Measurement and Modeling of Solubility of Galactose in Aqueous Ionic Liquids, 1-Butyl-3-Methyl Imidazolium Bromide, 1-Hexyl-3-Methyl Imidazolium Bromide and 1-Butyl-3-Methylimidazolium Chloride at T = (298.15 And 308.15) K - Mohammad Taghi Zafarani Moattar; Hemayat Shekaari; Elnaz Mazaher Haji Agha (Tabriz University of Medical Sciences, 2019)
Background: Saccharides are considered as abundant, cheap and renewable starting materials for chemicals and fuels. Recently, ionic liquids have been used as green solvents for saccharides. The solubility values of galactose in aqueous ionic liquid solutions are not available. Thus, the main objective of this research was to determine the solubility of galactose in aqueous solutions containing ionic liquids, 1-butyl-3-methyl imidazolium bromide, [BMIm]Br, 1-butyl-3-methylimidazolium chloride [BMIm]Cl and 1-hexyl-3-methyl imidazolium bromide, [HMIm]Br at different mole fractions of ionic liquids at T = (298.15 and 308.15) K. Methods: In this study, the gravimetric method was used to measure the solubility of galactose in aqueous ionic liquids solutions. Results: The solubility values of galactose in water and aqueous ionic liquid solutions were correlated with the activity coefficient models of Wilson, NRTL, modified NRTL, NRF-NRTL, and UNIQUAC. Conclusion: It was concluded that with increasing the mole fraction of ionic liquids, the solubility values of galactose decrease and in fact all of these ionic liquids show salting-out effect on aqueous galactose solutions and this behavior is stronger in ionic liquid 1-butyl-3-methylimidazolium chloride.